2019
DOI: 10.1155/2019/1562130
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Nanostructured Palladium and Other Metal Catalysts for Organic Transformation

Abstract: Nanocatalysis is an emerging field of research and is applicable to nearly all kinds of catalytic organic conversions. Nanotechnology is playing an important role in both industrial applications and academic research. The catalytic activities become pronounced as the size of the catalyst reduces and the surface area-to-volume ratio increases which ultimately enhance the activity and selectivity of nanocatalysts. Similarly, the morphology of the particles also has a great impact on the activity and selectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 158 publications
0
13
1
1
Order By: Relevance
“…Additionally, a biphasic aerobic oxidation of alcohols was performed by using palladium nanoparticles in a polyethylene glycol matrix as the catalyst and supercritical carbon dioxide as the substrate and product phase [ 29 ]. In contrast to our findings, however, it is well known that the aggregation of palladium nanoparticles, which results in a reduction in the surface area-to volume ratio, usually renders palladium nanoparticles less active and selective [ 33 ]. It was therefore suggested that other factors are responsible for the reaction enhancement effect, such as changes in the palladium oxidation state, palladium distribution on the surface, palladium nanoparticle morphologies, rate of nanoparticle formation, changes in the support structure, mass transfer limitations, etc.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Additionally, a biphasic aerobic oxidation of alcohols was performed by using palladium nanoparticles in a polyethylene glycol matrix as the catalyst and supercritical carbon dioxide as the substrate and product phase [ 29 ]. In contrast to our findings, however, it is well known that the aggregation of palladium nanoparticles, which results in a reduction in the surface area-to volume ratio, usually renders palladium nanoparticles less active and selective [ 33 ]. It was therefore suggested that other factors are responsible for the reaction enhancement effect, such as changes in the palladium oxidation state, palladium distribution on the surface, palladium nanoparticle morphologies, rate of nanoparticle formation, changes in the support structure, mass transfer limitations, etc.…”
Section: Resultscontrasting
confidence: 99%
“…Nanoparticles of palladium have been intensively studied in a wide range of catalytic applications, including C-C coupling reactions (e.g., Suzuki, Heck, Sonogashira, Negishi, Stille, Kumada and Hiyama), hydrogenation and electrochemical reactions in fuel cells [ 33 , 35 ]. There are also several reports showing the successful employment of palladium nanoparticles in oxidation reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As propriedades já conhecidas do paládio associada à escala nano que possui características próprias e muito vantajosas criam materiais muito interessantes e com um grande potencial de aplicação em diversas áreas. 43,44 . Geralmente, recebem o nome de nanopartículas materiais que possuem dimensões entre 1-100 nm.…”
Section: Introductionunclassified